Pengaturan Akad Mudharabah Muthlaqah pada Perbankan Syariah Perspektif Maqasid Asy-Syari’ah Jasser Auda - Erfina Fuadatul Khilmi (UIN Sunan Kalijaga Yogyakarta, 2021)
The low understanding of sharia principles towards the arrangement of Muthlaqah mudharabah agreements on Islamic banking has implications for immoral assumptions that view the youth as a mere 'guise' or 'mask' that is actually not much different from conventional banking. This is due to the incompatibility in the arrangement of muthlaqah mudharabah agreements on Islamic banking which shows obscurity and ambiguity. The purpose of this research is the foundation of the theoretical framework to understand aspects of maslahah values as an effort to improve the quality of Islamic banking regulation in order to achieve the welfare of society in line with religious ethical values. The purpose of this research is the foundation of the theoretical framework to understand aspects of maslahah value as an effort to improve the quality of Islamic banking regulation in order to achieve the welfare of society in line with religious ethical values. The research method used is a normative legal research method using a legal approach and a concept approach. The results of this research showed that the arrangement of mudharobah muthlaqah agreement on Islamic banking has not fully fulfilled the purpose or purpose of Maqashid Asy-Syari'ah Jasser Auda because the aspect of public information disclosure between customers and banks has not met the value of public goods that is the purpose of Maqashid.